OCULAR DRUG DELIVERY SYSTEMS: AN OVERVIEW - Maurya, Priyanka; Fatma, Saman; Sharma, Durgesh; Mishra, Jai Narayan; Kushwaha, Ashutosh (IJRDO-Journal of Applied Science, 2022)
The treatment for the ophthalmic diseases are topical route because of the various ocular barrier. Ocular drug delivery systems are considered as major challenges by today’s pharmacologist and formulation scientist. Topical eye drop is the most convenient and patient compliant route of drug administration, especially for the treatment of anterior segment diseases. tissues. In the past two decades, ocular drug delivery research acceleratedly advanced towards developing a novel, safe and patient compliant formulation and drug delivery techniques, which may surpass these barriers and maintain drug levels in tissues. There are many eye ailments which affected to eye and one can loss the eye sight also. Therefore, many ophthalmic drug delivery systems are available. These are classified as conventional and non- conventional (newer) drug delivery systems. Most commonly available ophthalmic preparations are eye drops and ointments about 70% of the eye dosage formulations in market. So overcome to these problems newer pharmaceutical ophthalmic formulation such as in-situ gel, nanoparticle, liposome, nanosuspension, microemulsion, intophoresis and ocular inserts have been developed in last three decades increase the bioavailability of the drug as a sustained and controlled manner.